2020
DOI: 10.1210/jendso/bvaa180
|View full text |Cite
|
Sign up to set email alerts
|

PCSK-9 Inhibitors in a Real-World Setting and a Comparison Between Alirocumab and Evolocumab in Heterozygous FH Patients

Abstract: A real-world setting study of Familial hypercholesterolemia (FH) patients which received PCSK9 inhibitors in a specialized referral center in Mexico City. Ten patients between the age of 18-70 years and a diagnosis of FH according to DLCN criteria with failure to achieve LDL-C goals with standard therapy between 2016 and 2017 enrolled in a simple randomization in which a group of five participants received alirocumab (75 mg every two weeks) and the remaining five patients evolocumab (140 mg every two weeks). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Likewise, some research has been undertaken with respect to routine clinical practice, including different population with hypercholesterolemia. Most reported real-life experiences are consistent with the clinical trials [ [21] , [22] , [23] , [24] , [25] , [26] , [27] ].…”
Section: Introductionsupporting
confidence: 59%
“…Likewise, some research has been undertaken with respect to routine clinical practice, including different population with hypercholesterolemia. Most reported real-life experiences are consistent with the clinical trials [ [21] , [22] , [23] , [24] , [25] , [26] , [27] ].…”
Section: Introductionsupporting
confidence: 59%
“…One possible explanation could be the increased compliance with the PCSK9 inhibitors or with the suggested therapy as a whole. Our data are in line with what has been previously reported in the literature 26 …”
Section: Discussionsupporting
confidence: 94%
“…Our data are in line with what has been previously reported in the literature. 26 The FOURIER cardiovascular outcomes trial studied evolocumab vs placebo in 27564 patients with clinically evident ASCVD and on a moderate-to-high-intensity statin regimen over a median follow-up duration of 2.2 years. The trial showed a mean percentage reduction in LDL-C levels with evolocumab, as compared with placebo; the reduction was 59%, from a median baseline value of 92 mg/dl to 30 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…PCSK9 inhibitors can be divided into those inhibiting the binding of PCSK9 to LDLR, and those inhibiting the expression or interfering with the secretion of PCSK9. PCSK9 monoclonal antibodies, alirocumab and evolocumab, were approved to treat FH in 2015 by the US Food and Drug Administration (FDA) [18]; however, the relationship between PCSK9 inhibitors and Lp(a) levels has not been fully studied [19]. Some studies indicated that evolocumab significantly reduces Lp(a) levels, more effectively than LDL-C plasmapheresis [20]; alirocumab reduced Lp(a) through an alternative pathway in addition to LDL-C reduction [21]; the ODYSSEY OUTCOMES demonstrated that Lp(a) predicted total cardiovascular event risk, and relative and absolute risk reduction in the placebo and alirocumab group [22]; while another showed no difference in circulating Lp(a) levels after 24 weeks of adalimumab or ezetimibe treatment [23].…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%